Transcriptome‑wide piRNA profiling in human gastric cancer - Lin, Xiandong; Xia, Yan; Hu, Dan; Mao, Qiao; Yu, Zongyang; Zhang, Hejun; Li, Chao; Chen, Gang; Liu, Fen; Zhu, Weifeng; Shi, Yi; Zhang, Huihao; et al. (Oncology reports, 2019)
Piwi‑interacting RNAs (piRNAs) comprise the largest class of non‑coding RNAs. They represent a molecular feature shared by all non‑aging biological systems, including germline and somatic cancer stem cells, which display an indefinite capacity of renewal and proliferation and are potentially immortal. They have been identified in animal stomachs, but their relationship with human gastric cancers remains largely unclear. The present study aimed to identify the piRNAs associated with human gastric cancers across the whole transcriptome. Fresh tumor tissues and adjacent non‑tumorous tissues from stomachs were examined using a piRNA microarray (23,677 piRNAs) that was then validated by qPCR. The differential expression of piRNAs between cases and controls was analyzed. The transposable elements (TEs) that are potentially targeted by the risk piRNAs were searched. The expression of the nearest genes that are complementary to the sequences of the piRNAs was examined in the stomach tissue. The regulatory effects of genome‑wide significant and replicated cancer‑risk DNA variants on the piRNA expression in stomach were tested. Based on the findings, we identified a total of 8,759 piRNAs in human stomachs. Of all, 50 were significantly (P<0.05) and differentially (>2‑fold change) expressed between the cases and controls, and 64.7% of the protein‑coding genes potentially regulated by the gastric cancer‑associated piRNAs were expressed in the human stomach. The expression of many cancer‑associated piRNAs was correlated with the genome‑wide and replicated cancer‑risk SNPs. In conclusion, we conclude that piRNAs are abundant in human stomachs and may play important roles in the etiological processes of gastric cancers.